Governance in Islam - "Siddiqi, M." (New Delhi, 2006)
Muslims means one who submits the will of God. Islam or the religion of muslims means submission to the will of God . Among other departments of life, governance is of great importance. Islam in governance also talks of submission to the leader since he is responsible for well being of his subjects. In this book author at length narrates basic structures of governance in Islam and how it distinguishes it from rest of the systems of governance practiced today. Considering the writings on Governance in Islam by author s deep study on the subject.
Keywords: Islam